Pengaruh Literasi Keuangan Syariah dan Kepercayaan Nasabah Terhadap Minat Penggunaan Mobile Banking Syariah di Bank Syariah Indonesia (BSI) KCP Bertais Mandalika - Muhamad Maimun, Bunga Aulia Khafifa; Muhammad Muhajir Aminy (Jurnal Perbankan Syariah, 2025)
The purpose of this study is to determine the effect of Islamic financial literacy and customer trust on the interest in using Islamic mobile banking at BSI KCP Bertais Mandalika. The variables in this study are Islamic financial literacy (X1), Trust (X2), and Interest in Using Islamic Mobile Banking (Y). The method in this study uses a quantitative method with an Associative approach or cause and effect influence. The population in this study were customers of Bank Syariah Indonesia KCP Bertais Mandalika who had not used Islamic mobile banking. The sample determination used accidental sampling. The data source used was primary data obtained from distributing questionnaires. The data analysis method was multiple linear regression analysis. The results of this study indicate that Islamic financial literacy partially has a significant positive effect on the interest in using Islamic mobile banking, and the trust variable partially has a positive and significant effect on the interest in using Islamic mobile banking. Simultaneously, Islamic financial literacy and trust have a significant positive influence on the interest in using Islamic mobile banking with an R-Square determination coefficient of 51.2%. Keywords: Literasi Keuangan Syariah, Kepercayaan, Minat